Disease State Psychological Knowledge And Health Belief On Cancer And Mindfulnessbased Stress Reduction (Mbsr) And Its Effects On Mindfulness, Anxiety, Depression And Health Related Quality Of Life (Hrqol) Among Cancer Patients In Penang, Malaysia: A Mix Methodology Approach - Othman, Che Noriah (2022)
Cancer is a death treatening disease world wide. Being diagnosed with cancer is a stressful event and if left unattended may lead to psychological distress and affect treatment compliance and clinical outcome. MBSR is proven clinically effective in reducing psychological distress problem among patients with various chronic diseases including cancer. Knowledge and health belief determine patients decission making. However to my thorough literatute search no study was conducted on cancer patients knowledge and health belief on cancer and MBSR in Malaysia especially in Penang. Also no data found that document the effects of MBSR on psychological distress including anxiety and depression among Malaysian cancer patients. So this study was conducted to explore the knowledge and health belief on cancer and MBSR and to measure the effect of MBSR program on HADS, CAMSR and HRQOL among cancer patients in Penang, Malaysia using a mix methodology approach. This study was conducted in three phases. Phase 1 is a qualitative phase which involved a face to face interveiewing the patients using a guided questionnaires and the saturation was reach at patients 18. Phase two was a quantitative survey using the questionnares developed from the phase 1 information.